2020
DOI: 10.1111/jmft.12431
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Care at a Distance: Student Therapists' Experiences of Learning and Delivering Relationally Focused Telemental Health

Abstract: There is mounting evidence that telemental health is an effective delivery method for treating a variety of mental, emotional, behavioral, and relational health problems. While many of the therapeutic skills leading to the effectiveness of face-to-face treatments are transferable, the effectiveness of telemental health requires unique skills. The purpose of this phenomenological study was to determine the experience of learning how to use videoconferencing to deliver relationally focused mental health care. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 25 publications
3
63
0
2
Order By: Relevance
“…6 From a practical point, registrars might find that the process of Intentionality , of being purposeful and vigilant in all aspects of the therapeutic endeavour, will inform their interaction with the patient. 4…”
Section: Adapting the Therapeutic Framementioning
confidence: 99%
See 4 more Smart Citations
“…6 From a practical point, registrars might find that the process of Intentionality , of being purposeful and vigilant in all aspects of the therapeutic endeavour, will inform their interaction with the patient. 4…”
Section: Adapting the Therapeutic Framementioning
confidence: 99%
“…Apprehension in preserving the therapeutic alliance (TA) via VC is a well-known phenomenon. 1,2,4 A small phenomenological study in 2020 found therapists had initial reluctance in their ability to establish TA via VC. 4 This was felt to be resolved by the completion of therapy courses, and is consistent with earlier studies that have found TA to be equivalent between in-person and VC.…”
Section: Therapeutic Alliancementioning
confidence: 99%
See 3 more Smart Citations